Pengaruh Pelatihan Regulasi Emosi Untuk Meningkatkan Subjective Well Being Pada Remaja Panti Asuhan Putri Pringsewu - Hasanah, Nur (ANFUSINA: Journal of Psychology, 2020)
Early adolescents generally experience changes in emotions and views about life satisfaction. Teenagers in orphanages are more prone to pressure so that their subjective well being will be lower. Emotional regulation training was able to increase focus and satisfaction as well as a sense of happiness which could increase teenagers' subjective well being. This study aims to determine the effect of emotional regulation training to increase subjective well being in Pringsewu orphanage children. The design of this study was a quasy experiment with a non-equivalent pre-post test with a control group. The subjects of this study were 40 girls in the Muhammadiyah Putri Prngsewu orphanage, which were divided into two groups, namely the intervention group and the control group. This training is carried out for three consecutive days. Data analysis used the T test. The results showed that in the intervention group the average subjective well being before the study was 67.15 ± 8.41 and increased after the study was 85.81 ± 9.17. In the control group the average subjective well being before the study was 65.67 ± 9.14 and increased at the time after the study 74.59 ± 12.25. There is a significant difference in changes in subjective well being in the intervention group and the control group (p value <0.05). There was an average increase in the intervention group that was greater than in the control group (p value <0.05). Thus, based on the statistical results, it can be concluded that there is an effect of emotional regulation training on increasing subjective well being among young women at the Pringsewu orphanage.